Peter the great and cataract surgery. Issue 2 (19th November 2019) - Grzybowski, Andrzej; Zimin, Igor; Leffler, Christopher T.
Abstract: Tsar Peter Alekseyevich Romanov (1672–1725), often called Peter the Great, modernized Russia in many areas, including in the field of medicine. Peter I attended medical lectures and demonstrations and may have even performed some medical procedures himself. In Paris, he witnessed a cataract couching performed by Englishman John Thomas Woolhouse (1664–1733/4) and requested that Woolhouse train a Russian student in ophthalmology.